Regioselective Three Component Domino Synthesis of Polyhydrospiro[indoline-3,3'-pyrrolizine]-2-one via [3+2] Cycloaddition Reaction - Tripathi, Vishwa Deepak; Shukla, Akhilesh Kumar; Mohammed, Hasan Shamran (Asian Journal of Chemistry, 2019)
In present work, we have reported the synthesis and characterisation of novel hexahydrospiro[indoline-3,3′-pyrrolizine]-2-one derivatives in good to excellent yields via [3+2] cycloaddtion reaction in regioselective manner. These compounds were synthesized via multicomponent reaction of substituted 3-cinnamoyl-4-hydroxy-6-methyl-2H-pyran-2-one, isatin, L-proline at room temperature. All the synthesized hexahydrospiro molecules were characterized by 1H and 13C NMR, IR spectra, mass spectra and elemental analysis. Regioselectivity in synthesized molecules were also explained on the basis of secondary orbital interactions. A simple and facile methodology is developed which has great importance in synthetic chemistry.